Determination of Zinc Requirement in Suckling Calves using Some Non-Linear Models - Mohammad Javad Elyasi; Khalil zaboli (پژوهشهای علوم دامی ایران)
Introduction: Currently, trace elements are provided to livestock with the aim of achieving optimal growth and enhancing performance in the majority of farm animals. Zinc (Zn) is one of these elements. It has been found that Zn is present within the structure of numerous enzymes and plays a crucial role in various essential physiological functions within the body. Regarding a low concentration of Zn in surface soils in Iran (less than 0.8 mg/kg), resulting in Zn deficiency in plants grown in these soils. Consequently, the consumption of these plants as animal feed can lead to Zn deficiency in the animals' bodies. Therefore, it is imperative to include Zn in the diet of all animals. However, one of the basic problems regarding for addition of Zn to the livestock diets in Iran is the lack of accurate knowledge of the livestock requirement for Zn (according to the country's geographical conditions). The present study was carried out to determine the optimal requirement of Zn in Holstein suckling calves using some models. Materials and Methods: In this experiment, a total of 30 Holstein suckling calves (5 treatments, n=6 calves/treatment) aged from 4 (42.75 ± 3.26 kg mean body weight) to 70 days (93.52 ± 3.97 kg mean body weight) were used in a completely random design. The experimental treatments consisted of zero (control), 15, 30, 45 and 60 mg Zn/kg DM of diet (in the form of zinc sulfate). The calves were fed with whole milk (approximately 10% of birth weight) in two equal meals daily at 08:00 and 19:00 and each calf's specific Zn requirement was supplemented to the evening meal milk in the form of zinc sulphate solution. Starter and fresh water were freely available for the calves throughout the experiment. The starter feed, provided in pellet form, consisted of a blend of corn grain, soybean meal, corn gluten, barley grain, wheat bran, sodium bicarbonate, and mineral and vitamin supplements. Additionally, chopped wheat straw (5%) and alfalfa hay (5%) incorporated into the starter feed from the 15th day of age until the weaning stage. During the experimental period, the calves' performance (including dry matter intake, average daily weight gain, feed conversion ratio and weaning weight) was systematically assessed. lood samples were taken from the jugular vein at the end of the trial (day 70) before the morning feeding for measurement of blood zinc and some parameters (glucose, urea, albumin and total protein) concentration.The performance of calves was assessed using simple broken line, quadratic broken line, and quadratic regression models. Subsequently, the Zn requirements for calves were estimated based on the optimal performance of calves as determined by these models. Results and Discussion: Results showed that the including Zn to the diet of calves had no significant effect on dry matter intake and feed conversion ratio. Also, no significant differences were observed among treatments for the concentration of glucose, urea, albumin and total protein in blood serum. But it significantly increased the average daily weight, blood zinc concentration and weaning weight of the calves (p<0.05). According to the analysis using a simple linear model, there was no statistically significant correlation between the Zn requirement and dry matter intake or daily weight gain. However, a significant correlation (p<0.05) was observed between the Zn requirement and weaning weight, as well as feed conversion ratio. Consequently, the Zn requirement for calves to achieve weaning weight and feed conversion ratio was determined to be 76.43 and 74.87 mg Zn/ kg DM in the diet, respectively. Based on the quadratic broken line model fitting, there was no statistically significant association between the Zn requirement for calves and their dry matter intake. However, a significant correlation was observed between the Zn requirement and other measured attributes (p<0.05). Consequently, the Zn requirement for daily weight gain, weaning weight, and feed conversion ratio was determined to be 83.96, 89.18, and 89.53 mg Zn/kg DM in the diet, respectively. Based on the quadratic regression model analysis, it was found that there was no statistically significant relationship between the Zn requirement and dry matter intake. However, a significant correlation was observed between the Zn requirement and other measured variables (p<0.05). Specifically, the Zn requirement for daily weight gain, weaning weight, and feed conversion ratio was determined to be 86.99, 79.50, and 86.99 mg Zn/kg DM in the diet, respectively. Fulfilling the Zn needs of calves resulted in optimal performance in terms of daily weight gain, weaning weight, and feed conversion ratio, with values of 759.2 g/d, 97.25 kg, and 2.21, respectively. Conclusion: Overall, these results showed that the optimal dietary Zn requirement for Holstein suckling calves falls within the range of 74.89-89.53 mg Zn/kg DM of diet. Furthermore, providing this level of Zn in the diet resulted in the highest performance in calves.​